Effect of gamma rays on the essential oil and biochemical characteristics of the Satureja mutica Fisch & C. A. Mey - Fatemeh Mahdi Navehsi; Vahid Abdossi; Bohloul Abbaszadeh; Razieh Azimi; Marjan Dianat (Scientific Reports, 2024)
Abstract There are 16 species in the genus Satureja L. (Lamiaceae), of which 10 are native. This research aimed to investigate the effect of gamma rays and storage conditions and duration on the percentage and components of the essential oil and some biochemical characteristics of Satureja mutica Fisch & C.A. Mey at the Research Institute of Forests and Rangelands. Plants were collected at the full flowering stage and exposed to different doses of gamma rays (0, 2.5, 5, 7.5, and 10 kGy) at the Atomic Energy Organization, Iran. The samples were kept in a refrigerator (4 °C) and in the shade (25 ± 2 °C) for 0, 120, and 240 h. This experiment was performed in a completely randomized design. Essential oil extraction was done by water distillation for 2 h. The composition of their essential oil components was identified using GC and GC/MS. Some biochemical traits, including phenol content, antioxidant capacity, and carbohydrate content, were measured. The results indicated that irradiation on the percentage of essential oil showed a statistically significant difference. In addition, the interaction effect of irradiation × storage conditions, irradiation × duration of storage, on the percentage of essential oil was significant. According to a comparison of the means, 2.5 kGy irradiation produced the highest percentage of essential oil (0.4%); in contrast, a significant decrease was detected in components with 7.5 and 10 kGy irradiation. It was observed that the percentage of some essential oil compounds decreased with the gamma-ray intensity increase. 2.5 kGy of gamma rays and shade storage conditions for 240 h led to the highest content of p-cymene and carvacrol. Nevertheless, the highest thymol content was obtained under refrigeration conditions without irradiation. The maximum phenol content and antioxidant capacity were obtained when the plants were irradiated with 2.5 and 7.5 kGy gamma rays. However, the maximum carbohydrate rate was observed in non-irradiated plants. It was concluded that low-intensity gamma rays could improve the percentage of essential oil and main components like p-cymene and carvacrol in S. mutica Fisch & C.A. Mey.